ChemInform Abstract: Direct Synthesis of 1, 4‐Diols from Alkenes by Iron‐Catalyzed Aerobic Hydration and C—H Hydroxylation. Issue 32 (24th July 2014) - Hashimoto, Takuma; Hirose, Daisuke; Taniguchi, Tsuyoshi
Abstract A broad variety of 1, 4‐diols are prepared from alkenes through an unique iron‐catalyzed aerobic hydration process.